The changing composition of regional employment - Clark, G (Clark University, 1984)
Non-production workers are an increasing proportion of total manufacturing employment. Lower labor productivity has been argued to be one consequence, although it has also been argued that more non-production workers are necessary to increase labor productivity. Many have also suggested that there are distinct industrial and geographical variations in non-production worker/production worker ratios although little has been presented by way of evidence. There are a number of contending explanations of the changing ratios, neoclassical and radical, and a great deal of confusion concerning cause and effect. Time-series adjustment models are developed for the period 1954-1976 and some four industries and thirty-four states to help clarify what causes changes in the composition of employment. Industry and geographical variations are, in fact, found in the significance and levels of effect of explanatory variables. And, it is found that capital intensification and profit rates are crucial positive determinants of changing NP/P ratios. However, it is also shown that it is very difficult to discriminate between competing explanations particularly in terms of their functional forms.